Effects of Maggot Therapy as a Novel Treatment Method for Cutaneous Leishmaniasis Lesions: A Review Study - Fereshteh Mohammadnejhad; Seyed Hassan Nikookar; Nasibeh Hosseini-Vasoukolaei (تحقیقات سلامت در جامعه, 2024)
Introduction and purpose: Leishmaniasis is classified as a neglected tropical disease caused by Leishmania protozoa and transmitted to humans by sandfly bites. The frequency of vectors, the high cost of drugs, long-term treatments, and drug resistance are some of the most serious obstacles to controlling this disease. In this regard, the present study investigated the effect of maggot therapy as a new method in the treatment of cutaneous leishmaniasis wounds. In maggot therapy, larvae of calliphorid flies are used to treat chronic wounds. Methods: The present study was a non-systematic review. Data were collected using the keywords “leishmaniasis”, “leishmania”, “maggot therapy” and “fly larvae” from PubMed, Ovid Medline, Web of Science, SID, and Scopus databases as well as Google Scholar search engine from 2008 to 2023. In this research, all published studies related to maggot therapy for the treatment of cutaneous leishmaniasis wounds were included and examined. Results: Larvae can help generate healthy new skin through tissue granulation in the wound bed. These larvae mechanically reduce the microbial load in the wounds through the movement of the oral appendages on the wound and at the same time by secreting proteolytic and anti-parasitic compounds, leading to wound healing. Conclusion: Maggot therapy is used to treat chronic wounds and has a healing effect. Since maggot therapy is a natural and low-cost option, it can be used as an alternative treatment method for patients with cutaneous leishmaniasis resistant to common drugs.